Exploring Barriers to Environmental Law Enforcement and Compliance in Nigeria Niger Delta Region - Edo, Zephaniah; Etemike, Laz; Clark, Victor E. (Journal of Danubian Studies and Research, 2022)
The important role of environmental enforcement in ensuring compliance with a country’s environmental policy cannot be over emphasised. The belief in many quarters that sustainable development is achievable, owes much to a country’s ability to enforce stringently its environmental laws. While Nigeria has several environmental laws regulating the activities of oil multinationals in the Niger Delta Region, there is widespread non-compliance with these laws. This paper looks at the various barriers mitigating against an effective environmental enforcement programme in the Niger Delta Region. It employs both secondary and primary sources in collecting data which were qualitatively analysed. Our findings shows that among other factors, corruption institutional inadequacy, legal loopholes, oil reliance, and lack of community awareness and participation are serious impediments to effective enforcement and compliance programme. The paper therefore recommends that government should make effort to address these barriers to ensure compliance with the law.